Faktor-Faktor yang Berhubungan dengan Kejadian Heat strain pada Pekerja Industri: Literature review - Nyndia Syafira Nofanto; Meirinia Ernawati (Lembaga Pengembangan Kinerja Dosen, 2026)
Hot work environments are a frequently overlooked health risk factor in Indonesia’s small and medium-scale manufacturing sector. This study aims to analyze the factors associated with heat strain incidents among industrial workers through a literature review of 8 national articles published between 2021 and 2025, sourced from Google Scholar, Garuda Kemdikbud, and institutional repositories. The results of the review indicate that workplace heat stress is the most dominant factor associated with heat strain, identified in 5 of the 8 analyzed articles. Inadequate water intake, high physical workload, and excessive work duration were also found to significantly contribute to the risk of heat strain. In addition, individual factors such as age, nutritional status, underlying health conditions, and medication use were found to influence workers’ susceptibility to heat strain, although the consistency of findings across studies remains variable. Environmental and organizational factors, particularly poor ventilation and insufficient workplace cooling systems, further exacerbate exposure to heat stress. The interaction between these physical and individual risk factors suggests that heat strain is a multifactorial occupational health issue rather than a single-cause condition. Therefore, managing heat strain requires a comprehensive approach that includes workplace environmental management, ensuring adequate fluid intake, regulating work-rest cycles, improving occupational safety supervision, and conducting regular health screenings to reduce long-term health risks among workers.